2022
DOI: 10.1063/5.0094527
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric efficiency in Bi-substituted La0.95Sr0.05CoO3

Abstract: We present the results of a comprehensive investigation of electric and thermal transport properties of polycrystalline Bi-substituted La0.95− xBi xSr0.05CoO3 for LBSCO-0, 1, and 2. The electrical resistivity reflects the semiconducting nature with n-type to p-type transition ∼52 K for LBSCO-1 and LBSCO-2 samples. In the low temperature region, the dominant transport mechanism is found to be variable range hopping with the hopping range decreasing with increasing temperature from 95 to 20 Å. The substitution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…, where r A and r B are the ionic radii of A and B cations and r O is the ionic radius of anion. 12 The obtained t of ∼0.88 supports the formation of distorted rhombohedral structure (0.71−0.9). The crystal structure of LCYO and LCIO is given in the Figure S2.…”
Section: ■ Results and Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…, where r A and r B are the ionic radii of A and B cations and r O is the ionic radius of anion. 12 The obtained t of ∼0.88 supports the formation of distorted rhombohedral structure (0.71−0.9). The crystal structure of LCYO and LCIO is given in the Figure S2.…”
Section: ■ Results and Discussionsupporting
confidence: 57%
“…The systematic lower Bragg angle shift of peaks for substitution of Y and In atoms with ionic radius of Co (0.54 Å), Y (0.9 Å), and In (0.8 Å) is noted (Figure S1). The degree of structural distortion in perovskite structure can be calculated using the Goldschmidt tolerance factor , where r A and r B are the ionic radii of A and B cations and r O is the ionic radius of anion . The obtained t of ∼0.88 supports the formation of distorted rhombohedral structure (0.71–0.9).…”
Section: Resultsmentioning
confidence: 91%
“…In recent years, perovskite structured oxide materials have demonstrated tremendous potential in thermoelectricity. 5,6 The general formula of perovskite material is ABO 3 , where A is a rare earth or alkali metal, and B is a transition metal. The ionic radius or charge balance of BO 6 is said to be a determinant of its octahedral arrangement by Anderson et al These materials have a variety of electronic structures, including insulators, semi-metals, and metals.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34][35] However, it has been shown by our group that on addition of Bi at the La site, the thermoelectric efficiency increases rapidly (ZT ∼ 0.17) due to a simultaneous increase in Seebeck coefficient S ∼ 354 mV K −1 and a decrease in thermal conductivity k ∼ 1.5 W m −1 K −1 . 36 In 2004, H. 26 These two works in the literature motivate us to study the magneto-thermoelectric properties of the Cr doped La 0.65 Bi 0.20 Sr 0.15 Co 1−x Cr x O 3 system and explore the possibility of tailoring the thermoelectric properties at lower temperatures ((50 K) using magnetic eld.…”
Section: Introductionmentioning
confidence: 99%
“…30–35 However, it has been shown by our group that on addition of Bi at the La site, the thermoelectric efficiency increases rapidly ( ZT ∼ 0.17) due to a simultaneous increase in Seebeck coefficient S ∼ 354 μV K −1 and a decrease in thermal conductivity κ ∼ 1.5 W m −1 K −1 . 36 In 2004, H. Fujishiro et al showed that the 5% Cr doped La 0.85 Sr 0.15 Co 0.95 Cr 0.05 O 3 (LSCCr x O) sample shows a comparatively high figure of merit ( Z value) relative to the pristine undoped La 0.85 Sr 0.15 CoO 3 sample. 25 Later in 2016, I. O. Troyanchuk et al demonstrated a large negative magnetoresistance (∼40%) at low temperatures (≲50 K) in Cr-doped La 0.5 Sr 0.5 Co 0.8 Cr 0.2 O 3 .…”
Section: Introductionmentioning
confidence: 99%